PWE-116 Gp210 and/or sp100 antibodies in primary biliary cirrhosis: predictors of cirrhosis/autoimmune (aih) overlap syndromes?. (22nd June 2015) - Taiwo, O; Mathew, S; Van Vlymen, J; Correa, A; Deacock, SJ; Berry, P; Cheent, K; Lewis, H; Ala, A
Abstract : Introduction: Primary Biliary Cirrhosis (PBC) is a progressive cholestatic liver disease, with Anti-mitochondrial antibodies (AMA) found in ∼ 95% of patients. Anti-GP210 and SP100 are suggested as additional markers in AASLD guidance, and may help in predicting disease prognosis. However, the role and benefit of anti-GP210 and SP100 testing in routine clinical practice is unclear. Method: We conducted a retrospective study of all PBC patients (diagnosed according to AASLD criteria), across 3 hospitals in Surrey, England; serving a population 1.1million. Prospective ELISA testing for GP210 and SP100 antibodies were undertaken on all active PBC-patients in follow-up. Baseline characteristics (laboratory/clinical) and progression during follow-up were analysed and compared between both groups. Results: 51 PBC patients were identified, with anti-GP210/SP100 demonstrated in 14 patients (27%); 9 with anti-SP100, 5 with anti-GP210. Demographic characteristics were similar between both groups: age 64 vs. 61 years, Females 80% vs. 70% in the PBC and GP210/SP100 groups. Consistent with the high sensitivity of AMA in PBC, only 1 (1/51) patient was AMA negative, and also negative for M2, GP210 and SP100. Baseline cirrhosis (imaging/biopsy) was present in 3/27 patients (11%) in the PBC group vs. 3/12 (25%) in the GP210/SP100 group. Quantitative mean M2 values were similar (100 vs. 96), as were baseline mean laboratory values (Bilirubin, ALT, ALP, GGT and IgM). Cirrhosis was present at follow-up (range 0.5–10 years) in 5/37 patients (13.5%) vs. 4/13 (31%) in the GP210/SP100 group. Treatment response to UDCA at one year (Barcelona criteria) was similar: 10/24 (42%) vs. 5/13 (38%) in the GP210/SP100 group. Post-treatment mean alkaline phosphatase levels were higher in the GP210/SP100 group 231 vs. 174 (p = 0.84). 8/51 PBC patients (16%) had diagnosed Autoimmune hepatitis (AIH)/PBC Overlap Syndrome (OS) (based on histological/serological features). OS cases were seen in 2/37 (5%) in the non-ANA group vs. 6/14 (43%) of those in the GP210/SP100 group, reaching statistical significance (p = 0.05); with no significant difference in ALT levels between the OS/non-OS groups. Conclusion: Although a small sample, our findings support the role of anti-GP210/SP100 as possible markers of disease severity (cirrhosis), and suggest a role for these auto-antibodies in identifying patients with PBC/AIH overlap syndromes; even in the absence of a significant transaminitis. Disclosure of interest: None Declared.